Grid stabilization with PMU signals - A survey - Gupta D.K.; Pandey R.K. (My University, 2025)
This paper presents critical survey along with the novel concept of smart power flow controller with Phasor Measurement Units (PMUs) signals for stability enhancement of a large power system. Also, the current status of Wide Area Measurement Systems (WAMS) and developments in real time applications of synchrophasor technology in power system has been adequately addressed. It has been noticed that with the help of synchrophasor technology, the system operators are now able to not only monitor and understand the transient/dynamic behaviour of the power system in real time at the control centres but also take quick restoration measures which was not possible in conventional SCADA system. PMUs deployment has shown encouraging results in recent contingencies, by way of assisting system operator with relatively better visualization, for Indian system. Thus, visibility of the network state at milliseconds level has enhanced the security, reliability and stability of the power system. This paper provides understanding of PMUs application and some novel research concept. © 2014 IEEE.